Gifted Girls’ Learning Experience in General Education - Undro, Evelina; Girdzijauskienė, Sigita (Acta Paedagogica Vilnensia, 2019)
The Munich Dynamic Ability-Achievement Model during the school period emphasizes the increasing impact of the school environment on the transformation of the ability (potential) of exceptional achievement, making it an integral part of the development of giftedness. However, the literature indicates that the identification and education of gifted children in Lithuania and abroad is often left to the personal discretion and initiative of teachers, parents or gifted students. In general education schools, gaps in teachers’ theoretical and practical training in gifted children education, as well as abilities to determine their academic and emotional needs, can be identified. Gifted are often seen as “awkward” students, and during adolescence they are faced with the need to choose between mimicking “normal teenage life” and being a “geek”. Gifted teens girls additionally feel pressured to conform to the “normal image of a girl” rather than displaying exceptional abilities and vigorously competing for achievement as “normal for the male image”. Teachers often think that boys can accomplish more than girls, so they need more reinforcement and encouragement. These factors pose a greater risk for gifted adolescent girls to be unrecognized, not properly promoted, and have not realized giftedness. A qualitative research strategy was used to reveal the authentic learning experience of gifted girls (teens) in general education schools. Six gifted girls from 13 years 10 months to 14 years 7 months, from three Vilnius schools, participated in the survey. The learning experience of gifted girls was revealed by three themes. They have shown that teachers’ attitudes that all students have equal learning needs, their obligation to help low achievers, and disbelief that gifted students need special education assistance had made gifted girls bored and waste time in the classroom. It was also revealed that the most commonly used methods of teacher training reflect a passive form of teaching that does not facilitate the process of acquiring knowledge. Finally, teacher indifference, high expectations, comparing students to gifted girls cause uncomfortable feelings, while teacher rigidity and insensitivity provoke conflict situations and reduce learning motivation. All of this, combined with inconsistent behaviour by applying different norms for themselves and students, widens the gap between “good” and “bad” students.